Silica-Supported Boron Trifluoride (BF3-SiO2): An Efficient, Environment Friendly and Recyclable Catalyst for The One-Pot Synthesis of 4(3H)-quinazolinones - Wu, Liqiang; Ma, Weiwei; Yang, Limin; Yan, Fulin (Asian Journal of Chemistry, 2010)
A simple and efficient synthesis of 4(3H)-quinazolinones has been accomplished by the one-pot condensation of anthranilic acid, triethylorthoformate and primary amines under solvent-free conditions in the presence of BF3-SiO2.